2015
DOI: 10.1371/journal.pone.0131861
|View full text |Cite
|
Sign up to set email alerts
|

Selective CNS Uptake of the GCP-II Inhibitor 2-PMPA following Intranasal Administration

Abstract: Glutamate carboxypeptidase II (GCP-II) is a brain metallopeptidase that hydrolyzes the abundant neuropeptide N-acetyl-aspartyl-glutamate (NAAG) to NAA and glutamate. Small molecule GCP-II inhibitors increase brain NAAG, which activates mGluR3, decreases glutamate, and provide therapeutic utility in a variety of preclinical models of neurodegenerative diseases wherein excess glutamate is presumed pathogenic. Unfortunately no GCP-II inhibitor has advanced clinically, largely due to their highly polar nature resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 71 publications
3
40
0
Order By: Relevance
“…24 Briefly, standard curves were prepared in naive plasma and brain tissues ranging from 10 to 50,000 nM. For extraction of 2-PMPA, plasma samples were thawed on ice, and then 50 μ L of the calibration standard or sample was transferred into silanized vials.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…24 Briefly, standard curves were prepared in naive plasma and brain tissues ranging from 10 to 50,000 nM. For extraction of 2-PMPA, plasma samples were thawed on ice, and then 50 μ L of the calibration standard or sample was transferred into silanized vials.…”
Section: Methodsmentioning
confidence: 99%
“…24 Briefly, samples and standards were reconstituted in 100 μ L of acetonitrile with vortex mixing followed by 50 μ L of MTBSTFA and were set to react at 60 °C in a water bath for 30 min. Upon completion of the reaction the samples were then centrifuged again at 10,000 rpm at 5 °C for 2 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the greater efficacy of NAAG may stem from improved brain penetration achieved with nasal versus intraperitoneal drug administration (Lochhead and Thorne 2012). Indeed, Rais and colleagues (2015) recently showed that nasal delivery of 2-PMPA resulted in significantly higher concentrations of the drug in brain tissue compared to an equivalent dose given by intraperitoneal injection. Certainly, it would be of interest to determine whether nasal relative to intraperitoneal administration of 2-PMPA has greater efficacy against the behavioral effects of MDPV, as well as other psychostimulants.…”
Section: Discussionmentioning
confidence: 99%